PENEGAKAN HUKUM PROGRESIF: UPAYA MEWUJUDKAN KEADILAN SUBSTANTIF - H.A Malthuf Siroj; Ismail Marzuki (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2017)
Law enforcement that often miseries and hurts the sense of community justice encourages one of the jurists, Satjipto Rahardjo expresses his idea about the need to involve conscience and morals in punishment. This way of punishment is then referred to as progressive law enforcement. Progressive law is a scientific endeavor that criticizes conventional punishment mechanisms; namely punish by putting forward the legal-formal truth, which is the cause of law enforcement in this country cannot give happiness to the seekers of justice. The progressive legal orientation is how to ground the truth (substantive justice), based on the premise that law is for man, not on the contrary. In addition, progressive legal notion holds that the truth of the law is not always judged from the application of laws formulated in the law, but the extent to which the law responds to developments in society. To that end, when the law is stuck in answering the community's problem, then here is the need to make a breakthrough (rule breaking). This shows that progressive law enforcement is an effort / process that always seeks truth and justice.Keywords: Law Enforcement, Progressive Law, Substantive Justice